Laparoscopic cholecystectomy during pregnancy - Habash, Mohammed Mohammud; Saadi, Raakad Kamel (International Journal of Psychosocial Rehabilitation, 2020)
Laparoscopic cholecystectomy is the definitive treatment method for treatment of symptomatic gallstone disease. Pregnancy is a prolithogenic state; estrogen increases cholesterol production, whereas progesterone reduces bile acid secretion and inhibits gallbladder emptying. Thus, the most common causes of gall bladder disease in pregnancy are gall stones and biliary sludge. The aim of the present study was to evaluate the correlation between correlations of cesarean section pregnancy surgery with laparoscopic cholecystectomy. In the present study, the female patients (n=100) visited to the Al- Shafa Hospital Diyala/ Iraq during July 2018 to July 2019 were enrolled. The ages of the pregnant women were 20 to 36 years. Before surgery, the red blood cells, white blood cells and serum urea were found to be 104.57±2.91; 12658.0±1674.4 and 33.48±0.47, respectively. After surgery, the red blood cells, white blood cells and serum urea were found to be 221.9±10.91; 10183.9±1053.6 and 34.94±0.44, respectively (Table 2).